(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
The development of writing skills at school is essential in shaping students into effective communicators, capable of expressing their thoughts, ideas, and emotions with clarity. Writing is a necessary way to learn English. Regularly writing can help pupils to broaden their horizon and they can get higher score any exams. This article highlights the importance of writing skills not only for academic success but also for future professional and personal achievements. It discusses how schools foster these skills through curriculum integration, writing workshops, peer reviews, access to resources, and extracurricular activities. Success stories are also shared to illustrate the impact of these initiatives. The article concludes by emphasizing that investing in writing skills equips students with the tools they need to succeed in an increasingly complex world.